Increasing Agricultural Productivity by Building Capacity among Peasants in Mbozi District, Tanzania - David Msokwe; Florence Sitima (Agricultural Sciences: Techniques and Innovations Vol. 1, 2025)
Capacity building in the agriculture sector is crucial for Tanzania because the sector has been playing an important role as a key driver for the economic growth of the nation since its independence. Different strategies for capacity building have been adopted by the country to raise agricultural productivity. Numerous studies have looked into capacity-building tactics and how they affect agricultural output. However, little is known about how capacity building might increase agricultural output in developing nations. This study provided an opportunity to examine capacity building and how it affects Tanzanian agricultural productivity. It specifically examined the association between capacity building and agricultural productivity in Mbozi District, identified the strategies for capacity building for agricultural productivity in Mbozi District and underlined the mechanisms through which capacity building translates into productivity gains in Tanzania, a case of Mbozi District. Both qualitative and quantitative methods were used in the study’s data collection and analysis. The primary data was collected by administering questionnaires to 300 (200 males and 100 females) peasants in November 2020. Interviews, observations, and an examination of documents were used to gather data. The Statistical Package for Social Sciences, version 20, was used to examine descriptive and inferential statistics gathered from 300 peasants. Qualitative data was analysed using a content analysis approach, which aided in quantitative data measurement and reasoning. With the employment of contemporary farming, harvesting, and storage techniques, capacity building affects agricultural productivity, according to a p-value of 0.000. The study revealed that inadequate or absent capacity-building strategies contribute to low productivity, while well-implemented strategies—including training in modern farming, harvesting, and storage techniques—lead to substantial improvements. The study also revealed that knowledge of agricultural production among peasants was low, and that is why productivity remains low despite enough fertile soil in the district. The observations also showed that strategies like training and farm field schools were insufficient in the region due to the large number of peasants. This was mostly remarked in the rural areas in the sense that many strategies were more centred in the urban areas compared to rural areas, with a large number of peasants and endowed with much potential for production. Stakeholders advocate the use of the best seeds, skills on edaphic factors, equipment, farm field schools, and research and workshops as strategies in capacity building. In addition, the involvement of academia, researchers, and political leaders increased agricultural productivity. These results imply that raising productivity requires a combination of different individuals, private and public institutions. Therefore, capacity building is inevitable among peasants in order to raise productivity. It is recommended that impact assessment be incorporated because it helps in reviewing and amending land and agricultural policies. Online training is recommended as an alternative to the shortage of trainers to build capacity among more peasants.